2014
DOI: 10.1007/s10549-014-2898-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection and clinical relevance of hematogenous tumor cell dissemination in patients with ductal carcinoma in situ

Abstract: Hematogenous tumor cell dissemination is a crucial step in systemic disease progression and predicts reduced clinical outcome in breast cancer patients. Only invasive cancers are assumed to shed tumor cells into the bloodstream and infiltrate lymph nodes. However, recent studies revealed that disseminated tumor cells (DTCs) may be detected in bone marrow (BM) of patients with preinvasive lesions, i.e., ductal carcinoma in situ (DCIS). The purpose of this analysis was to examine the incidence and clinical value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
1
11
0
6
Order By: Relevance
“…Interestingly, the frequency of DCIS with disseminated tumor cells (25.0%) did not significantly differ from that of invasive breast cancer (19.6 %; p = 0.57). Despite caution should be taken because of the very small sample size in our study, this observation supports previous results of early dissemination and systemic spread already in pre-invasive disease [18][19][20][21].…”
Section: Comparison Of Clinical Parameters and Biomarkers Between DCIsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, the frequency of DCIS with disseminated tumor cells (25.0%) did not significantly differ from that of invasive breast cancer (19.6 %; p = 0.57). Despite caution should be taken because of the very small sample size in our study, this observation supports previous results of early dissemination and systemic spread already in pre-invasive disease [18][19][20][21].…”
Section: Comparison Of Clinical Parameters and Biomarkers Between DCIsupporting
confidence: 92%
“…This result seems counterintuitive and sample size is again an issue here. But beside potential technical and statistical issues similar data have been obtained before [18][19][20][21]28] suggesting that profound but undetectable dissemination may occur very early. Our results also hint towards a better prognosis of luminal type tumors both in DCIS and invasive breast cancer.…”
mentioning
confidence: 56%
“…Support for the notion that breast cancer dissemination can occur in pre-invasive stages of tumour progression comes from the consistent finding of circulating tumour cells in the peripheral blood (or in the bone marrow) of patients with DCIS. In six studies (range 19–404 patients), between 13 and 25% of DCIS patients were found to have circulating tumour cells [ 29 34 ]. It has been proposed that such cells derive from an occult (micro)-invasive lesion within DCIS.…”
Section: Part 2: the Seer Study: Mortality After Dcismentioning
confidence: 99%
“…Individual tumour cells reaching the blood vessels and their subsequent dissemination are important steps in the metastatic cascade. According to studies, pre-invasive lesions of the breast, such as ductal carcinoma in situ (DCIS), can be accompanied by tumour cell dissemination 2 , 18 , so that haematogenous tumour cell dissemination is considered an early event in the course of malignant disease. The CellSearch system can detect circulating tumour cells in 20 – 30% of patients with non-metastatic breast cancer 19 ( Table 2 ).…”
Section: Clinical Applications Of Liquid Biopsy In Early Breast Cancementioning
confidence: 99%
“…The so-called “Halsted Doctrine”, which viewed breast cancer as a local event with healing only possible by the most radical surgery, was replaced by the “Fischer Doctrine”, which regards even early stage breast cancer as a systemic disease 1 . Today we know that haematogenous dissemination already takes place in very early stages of breast cancer and that the circulating tumour cells (CTCs) will even be found in patients with pre-invasive breast lesions 2 . At the same time the hypothesis of metastatic inefficiency states that most of these cells are eliminated by the immune system or the mechanical shear forces in the blood 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%